Ground subsidence due to uniform fluid extraction over a circular region within an aquifer. (April 2015) - Selvadurai, A.P.S.; Kim, Jueun
Highlights: Analytical solution for poroelastic subsidence due to circular fluid extraction. Numerical results for ground subsidence with depth and area-dependent extraction zone. Comparative results for circular extraction and point sink problems. Validation of computational approach using analytical results. Abstract: This paper examines the ground subsidence caused by the uniform extraction of fluids from a disc-shaped region located within a poroelastic halfspace. Biot's theory of poroelasticity is used to examine the problem. The fluid extraction over the circular region at the interior of the poroelastic domain induces time-dependent axisymmetric surface settlements. The theoretical results are also used to examine the accuracy of a multi-physics computational scheme that can be used to examine more complex geological settings.